2020
DOI: 10.1001/jamaoncol.2020.2436
|View full text |Cite
|
Sign up to set email alerts
|

Pembrolizumab in First-line Gastric Cancer

Abstract: intensified adjuvant (chemo)radiotherapy versus standard adjuvant chemoradiotherapy post transoral minimally invasive surgery for resectable HPV-positive oropharyngeal carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…In addition, we found that patients with PD-L1 combine positive score (CPS) > 10 could benefit more from PD-1 or PD-L1 immunotherapy (Shitara et al, 2020;Janjigian et al, 2021;Moehler et al, 2021). Elizabeth C et al also analyzed the results of KEYNOTE-062 and found that AGC patients with PD-L1 combined positive score (CPS) more than 10 or greater could benefit more from pembrolizumab than patients with a CPS of 1 or greater (Smyth and Moehler, 2020). To evaluate the expression difference of immune checkpoint genes, we compared the expression of immune checkpoint genes between the low-risk and high-risk patients.…”
Section: Clinical Value Of the Risk Model In Immunotherapymentioning
confidence: 86%
See 1 more Smart Citation
“…In addition, we found that patients with PD-L1 combine positive score (CPS) > 10 could benefit more from PD-1 or PD-L1 immunotherapy (Shitara et al, 2020;Janjigian et al, 2021;Moehler et al, 2021). Elizabeth C et al also analyzed the results of KEYNOTE-062 and found that AGC patients with PD-L1 combined positive score (CPS) more than 10 or greater could benefit more from pembrolizumab than patients with a CPS of 1 or greater (Smyth and Moehler, 2020). To evaluate the expression difference of immune checkpoint genes, we compared the expression of immune checkpoint genes between the low-risk and high-risk patients.…”
Section: Clinical Value Of the Risk Model In Immunotherapymentioning
confidence: 86%
“…First-line treatment of PD-1/ PD-L1 inhibitors could prolong OS and PFS of GC patients with CPS>10 or MSI-H (Shitara et al, 2020;Janjigian et al, 2021;Moehler et al, 2021). Results from a randomized phase III KEYNOTE-062 study indicated that AGC patients with a combined positive score (CPS) more than 10 or greater could benefit from first-line pembrolizumab (Smyth and Moehler, 2020). Huang et al reviewed the efficacy and safety of third-line treatments for advanced gastric cancer (AGC).…”
Section: Introductionmentioning
confidence: 99%
“…While these results in aggregate represent substantial additions to treatment options, there remains much uncertainty about when single-agent ICPI without chemotherapy might be favorable, or when immunotherapy might have a low probability of benefit. While higher PD-L1 levels identify patients with favorable outcomes with ICPI-containing regimens compared to chemotherapy alone in all of these studies, concerns around spatial and temporal PD-L1 heterogeneity support a need for more rigorous assessments with other candidate biomarkers, such as tumor mutational burden (TMB) and microsatellite instability high (MSI-H) (4). Currently, the National Comprehensive Cancer Network (NCCN) does not endorse single-agent ICPI without chemotherapy as an option in 1 st line settings.…”
Section: Introductionmentioning
confidence: 99%
“…In France, the ongoing GASTFOX phase III study will compare TFOX versus FOLFOX as the first‐line chemotherapy for patients with advanced gastric or GEJ adenocarcinoma 35 . Given the recent results of immunotherapy, 28,36,37 this therapeutic sequence seems to be the most interesting for the development of trials for future strategies that include immunotherapies, depending on the combined positive score, as suggested in an editorial 38 . Since FOLFIRI is a standard of care after doublet or triplet platimun‐based first line, it is relevant to combine FOLFIRI with immunotherapy as in the DURIGAST trial 39 recently communicated at the ESMO 2022 congress 40 .…”
Section: Discussionmentioning
confidence: 99%
“… 35 Given the recent results of immunotherapy, 28 , 36 , 37 this therapeutic sequence seems to be the most interesting for the development of trials for future strategies that include immunotherapies, depending on the combined positive score, as suggested in an editorial. 38 Since FOLFIRI is a standard of care after doublet or triplet platimun‐based first line, it is relevant to combine FOLFIRI with immunotherapy as in the DURIGAST trial 39 recently communicated at the ESMO 2022 congress. 40 Immunotherapy is now essential in the treatment of gastric adenocarcinoma, it remains to define the best combinations and the best sequences of associated chemotherapy.…”
Section: Discussionmentioning
confidence: 99%